Comparisons of recent global geopotential models with terrestrial gravity field observations over New Zealand and Australia - Amos, Matthew; Featherstone, Will (Institution of Surveyors, Australia, 2003)
This study compares global geopotential models (GGMs) released between 1996 and 2002, including four that incorporate data from the CHAMP dedicated satellite gravimetry mission, with terrestrial gravity field-related data over Australia and New Zealand. The GGM-implied gravity anomalies are compared with point free-air gravity anomalies on land; geoid heights compared with discrete geometrical heights from co-located GPS and sprit-levelling data on the local vertical datums; and absolute (Pizzetti) deflections of the vertical at the geoid are compared with absolute (Helmert) vertical deflection estimates at the Earth’s surface. The results indicate that EIGEN-2, which uses purely CHAMP data, is currently the best satellite-only GGM over Australia and New Zealand (acknowledging the presence of long-wavelength errors in the “control” data), whereas the various combined high-degree GGMs are not statistically significantly different from one another over Australia and New Zealand. A hybrid GGM was created from EIGEN-2 to degree 32 and EGM96 from degree 33 to 360, where the cut off was selected using the global error degree variances of each. This GGM makes a very slight improvement on all others, and thus will probably be used in near-future Australian and New Zealand geoid models